IMPERATIVE POLITENESS OF TEACHERS IN THE TEACHING AND LEARNING PROCESS IN THE CLASSROOM - Abd. Rahman Rahim (SEAN Institute, 2022)
When it comes to communication, especially the contact that occurs between teachers and students during the process of teaching and learning, politeness is one of the aspects that needs to be taken into consideration. The purpose of this research is to identify and describe the form of imperative speech used by teachers during the teaching and learning process, as well as to investigate the factors that contribute to violations of imperative politeness committed by teachers toward students during the teaching and learning process. The present investigation is a qualitative descriptive study, and the data comes in the form of transcripts of the instructor's comments made during the course of instruction. According to the findings of the study, educators are more likely to violate the conventions of linguistic politeness when they address pupils with urgent speech. This is evident from the total number of utterances. [Citation needed] There were a total of 120 utterances discovered, 96 of which were in violation of the linguistic politeness guidelines, and 24 of which complied with the guidelines..